KAJIAN LITERATUR : DOMINASI BAHASA DIGITAL DALAM KOMUNIKASI SISWA SERTA DAMPAKNYA TERHADAP KETERAMPILAN MENULIS SISWA DI SEKOLAH DASAR - Fadhilah, Inayah; Azzahra, Khalila; Habibi, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the dominance of digital language in elementary school students’ communication and its impact on their writing skills. The rapid growth of digital technology has significantly influenced students’ communication patterns through the frequent use of abbreviations, slang, emojis, and mixed languages in online interactions. This research aims to analyze how digital language affects students’ formal writing abilities and to identify the role of educators in guiding appropriate language use. The study employed a qualitative approach using a Systematic Literature Review (SLR) method based on the PRISMA framework. Data were collected from scientific articles published between 2020 and 2026 through academic databases such as Google Scholar, Portal Garuda, and Semantic Scholar. The findings indicate that digital language has both positive and negative impacts on students’ writing skills. Positively, digital media can enhance creativity, motivation, literacy engagement, and communication efficiency through interactive learning tools. However, excessive use of non-standard language may reduce students’ mastery of formal Indonesian writing, including spelling accuracy, sentence structure, and adherence to language conventions. The results also reveal that factors such as the intensity of gadget use, learning environment, and teacher supervision strongly influence these outcomes. Therefore, teachers play a crucial role in balancing the integration of digital language and formal language instruction in elementary education. The study concludes that digital language significantly affects students’ writing development and requires proper educational strategies to support effective language learning.